Analysis of Spatial Diversification of Organic Farming Development in the Communes of the Lodzkie Voivodeship - Antczak, Elżbieta (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
The paper analyses the spatial diversification of organic farming development in the gminas of the Lodzkie voivodeship in years 2008–2016. The level of the studied phenomenon was defined by a synthetic measure based on the zero unitarization method. The spatial interactions with using the Moran’s I statistics were also examined. These spatial links may result from natural conditions, range of the agricultural area, subsidies or gminas cooperation. Data was obtained from the Main Inspectorate of Trade Quality of Agricultural and Food Products and the Central Statistical Office. The presented phenomenon was described by 28 sub measurements, which determined the ecological crop cultivation, animal maintenance and eco‑production. Despite the gminas have an enormous potential in organic production, the region is characterised by a large diversity of the phenomenon and the lack of visible trends in the development of this agricultural system. The strengths of the eco‑agriculture of Lodzkie are, e.g. ecological cultivation of fruit trees and shrubs, production of grass, cultivation of feed cereals and plants, cattle breeding for meat and milk, pigs and meat production. The values of the synthetic measure distinguished high potential gminas, e.g. Krzyżanów, Grabów, Wielgomłyny and Nieborów. Finally, the statistically significant spatial relations were also detected. The key units creating in the space a high‑high cluster of the phenomenon were, e.g. Żarnów, Klonowa, Ładzice, Paradyż, Tuszyn and Dalików.